Adverse effects in the fish embryo acute toxicity (FET) test: a catalogue of unspecific morphological changes versus more specific effects in zebrafish (Danio rerio) embryos - Hellfeld, Rebecca von; Brotzmann, Katharina; Baumann, Lisa; Strecker, Ruben; Braunbeck, Thomas (Environmental sciences Europe, 2020)
The Fish Embryo Acute Toxicity (FET) test with the zebrafish (Danio rerio) embryo, the OECD test guideline (TG) 236, has been designed as an alternative for acute fish toxicity testing such as the OECD Acute Fish Toxicity Test (TG 203). To provide equivalent sensitivity to the acute fish test, the original FET test was designed to use only four morphological core endpoints: coagulation of the embryo, lack of somite formation, lack of heart beat, and non-detachment of the tail. These endpoints were selected due to (1) their association with mortality, directly or indirectly, (2) improve the practicality for screening by well-trained technical staff, and (3) the endpoints being relatively simple morphological alterations.
Gesehen am 04.11.2020